Tikrari Method to Improve Memorization Qur’an at MI Al-Huda Sidoarjo - Valensiana Ustoyo; Lailatuz Zuhro; Mufidatus Sholikhah (eL Bidayah: Journal of Islamic Elementary Education, 2020)
This research is a classroom action research that aims to improve students' memorization ability in fourth grade A class at MI Al Huda Sidoarjo. The material is "Let's Memorize Surah Al-’Adiyat " through Tikrari method. This study used 41 subjects in fourth grade A class at MI Al Huda Sidoarjo on the subject lesson Al-Qur'an Hadith. Researchers used two cycles, each cycle consisting of : (1) Planning, (2) Action, (3) Observation, and (4) Reflection. The researchers collected data using interviews, observations, non-test assessments (performances), and documentation. The results of this study found that : a) The use of the Tikrari method can be used to improve the students’ ability in memorizing surah Al-' Adiyat with a positive increase in both student and teacher activities, b) The ability to memorize students increases in the high category with an increase of 43.9% during pre-cycle to second cycle. The conclusion of this study is the Tikrari method can improve students' memorization ability on the material "Let's Memorize the Surah Al-'Adiyat” in the subject lesson Al-Qur'an Hadith in fourth grade A class at MI Al Huda Sidoarjo. [Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk meningkatkan kemampuan menghafal siswa MI, materi “Mari Menghafal Surah Al-‘Adiyat” melalui metode Tikrari. Penelitian ini menggunakan subjek sebanyak 41 siswa kelas IV-A di MI Al Huda Sidoarjo pada mata pelajaran Al-Qur’an Hadits. Peneliti menggunakan dua siklus, setiap siklus terdiri dari : (1) Perencanaan, (2) Tindakan, (3) Observasi, dan (4) Refleksi. Dalam pelaksanaannya, peneliti mengumpulkan data dengan menggunakan wawancara, observasi, penilaian non tes (unjuk kerja atau performances), dan dokumentasi. Hasil dari penelitian ini ditemukan bahwa : a) Penggunaan metode Tikrari dapat digunakan untuk meningkatkan kemampuan menghafal siswa surat Al-‘Adiyat dengan adanya peningkatan positif dari aktivitas siswa dan guru, b) Kemampuan menghafal siswa meningkat dalam kategori tinggi dengan peningkatan sebesar 43,9 % dari pra siklus hingga siklus II. Kesimpulan dari penelitian ini adalah metode Tikrari dapat meningkatkan kemampuan menghafal siswa pada materi “Mari Menghafal Surah Al-‘Adiyat” mata pelajaran Al-Qur’an Hadits kelas IV-A di MI Al Huda Sidoarjo.]